2009
DOI: 10.1002/pmic.200700903
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the proteome of pea mature seeds reveals the phenotypic plasticity of seed protein composition

Abstract: Pea (Pisum sativum L.) is the most cultivated European pulse crop and the pea seeds mainly serve as a protein source for monogastric animals. Because the seed protein composition impacts on seed nutritional value, we aimed at identifying the determinants of its variability. This paper presents the first pea mature seed proteome reference map, which includes 156 identified proteins (http://www.inra.fr/legumbase/peaseedmap/). This map provides a fine dissection of the pea seed storage protein composition reveali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
85
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(98 citation statements)
references
References 53 publications
9
85
1
3
Order By: Relevance
“…An observation common to 2-DE gels, and pertinent to the analysis of the SSP proteome in Gossypium, is that numerous spots often correspond to isoforms of the same protein accession, as previously demonstrated with 2-DE analyses of SSPs in pea, soybean, rapeseed, and Arabidopsis (Hajduch et al 2005(Hajduch et al , 2006Higashi et al 2006;Bourgeois et al 2009). By contrasting the isoform peptide sequences obtained through MS analysis to the full-length proteins, the on-gel spot location and the computationally predicted location can be examined to determine the formation and features of SSP isoforms, used here to characterize the isoforms of the vicilins (Figure 7).…”
Section: Detailed Proteomic Characterization Of Gossypium Sspsmentioning
confidence: 96%
See 1 more Smart Citation
“…An observation common to 2-DE gels, and pertinent to the analysis of the SSP proteome in Gossypium, is that numerous spots often correspond to isoforms of the same protein accession, as previously demonstrated with 2-DE analyses of SSPs in pea, soybean, rapeseed, and Arabidopsis (Hajduch et al 2005(Hajduch et al , 2006Higashi et al 2006;Bourgeois et al 2009). By contrasting the isoform peptide sequences obtained through MS analysis to the full-length proteins, the on-gel spot location and the computationally predicted location can be examined to determine the formation and features of SSP isoforms, used here to characterize the isoforms of the vicilins (Figure 7).…”
Section: Detailed Proteomic Characterization Of Gossypium Sspsmentioning
confidence: 96%
“…This exaggerated interspecific expression variation observed in the Gossypium seed proteomes, when compared to similar research in Brassica, which revealed 15% divergence between diploid species and only 1% between the synthesized allotetraploid B. napus and its diploid progenitors (Albertin et al 2006), may reflect a gradual accumulation pattern of differential protein expressions in allopolyploid cotton naturally formed 1-2 million years ago vs. newly synthesized B. napus, as well as, at least in part, differences in the tissues examined. That is, the stem and root proteomes studied in Brassica are likely more complex with respect to their proteomes than are the seed proteomes studied here, which tend to be composed of fewer protein types that are extensively modified into many isoforms (Hajduch et al 2005;Higashi et al 2006;Bourgeois et al 2009;Larre et al 2010). Thus, relatively few underlying differences in post-translational modification programs among cotton species may propagate to affect multiple isoforms, in the process generating a relatively large impact on inferences of similarity, at least in comparisons of seed vs. stem or root proteomes.…”
Section: Biased Accumulation Of D-genome Proteins In Polyploid Cottonmentioning
confidence: 99%
“…More comprehensive sequence information also permits the analysis of various posttranslational modifications that occur and increase the number of polypeptides arising from a single sequence. A reconstruction of posttranslational modifications leading to the deposition of mature globulins was elegantly demonstrated by Dam et al (2009) in L. japonicus and by Bourgeois et al (2009) in pea (Pisum sativum). Dam et al (2009) also compared the protein compositions of green and mature seeds using gel filtration liquid chromatography/tandem mass spectrometry (MS/MS) and identified 920 proteins from green and 264 proteins from mature seeds.…”
Section: The -Omics Technologies Applied To Legume Seedsmentioning
confidence: 99%
“…In wheat, high temperatures increase the level of globulin protein storage causing a reduction of the albumin/globulin content in mature seeds (Hurkman et al, 2009;Stone & Nicolas, 1996). In pea, the final level of vicilin storage proteins was higher under heat stress (Bourgeois et al, 2009). High temperature during seed filling also affects the accumulation level of stress/defense proteins, like heat shock proteins (Bourgeois et al, 2009;Hurkman et al, 2009;Majoul et al, 2003).…”
Section: High Temperatures Affect Both Seed N Concentration and Compomentioning
confidence: 99%
“…In pea, the final level of vicilin storage proteins was higher under heat stress (Bourgeois et al, 2009). High temperature during seed filling also affects the accumulation level of stress/defense proteins, like heat shock proteins (Bourgeois et al, 2009;Hurkman et al, 2009;Majoul et al, 2003). The magnitude in which a heat stress during seed filling period affects seed quality depends on the heat tolerance of the genotype, the intensity and the timing of heat stress (Stone & Nicolas, 1996;Passarella et al, 2002;Spiertz et al, 2006).…”
Section: High Temperatures Affect Both Seed N Concentration and Compomentioning
confidence: 99%